AN EFFECTIVE ANTI-FRAUD PROGRAM: HOW DO WE KNOW? (THE CHALLENGE OF FINDING AN ANTI-FRAUD PROGRAM IN THE INDONESIAN PUBLIC SECTORS) - Dedy Eryanto (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
As one of the most serious frauds in many public sector institutions, corruption has been viewed as the 'public enemy’ for the last two decades in Indonesia. Many anti-fraud programs have been attempted to counter these corrupt activities. However, to what extent the programs are successful to bring the Indonesian public sectors to become ‘a clean institution’, has not been known yet. Therefore, by applying the OECD Integrity Management System as a framework and semi-structured interviews, this study provides an empirical studyat a strategic public institution. This study also attempts to analyse some factors that have become challenges in many anti-fraud programs for public sector in many developing countries like Indonesia.